The Role of Indonesian Constitutional Court in Resolving Disputes among the State Organs - Iwan Satriawan; Khairil Azmin Mokhtar (Hasanuddin Law Review, 2019)
The paper attempts to assess the role of the Constitutional Court of Indonesia in the process of consolidating democracy in the country. Examinations are made on the court’s decisions regarding dispute concerning jurisdiction among state organs. This paper argues that the Constitutional Court has not made a significant impact on the promotion of democracy. It is believed that the failure of the Court to consolidate democracy through its decisions regarding dispute concerning jurisdiction among state organs could be attributed to two main reasons. The first is due to the unclear concept of subjectum litis of the petitioners to have legal standing in the Constitutional Court, and the second is the lack of understanding of the subject matter jurisdiction of the Court. Due to uncertainties only, small numbers cases registered and heard by the Constitutional Court. Furthermore, most of the cases registered in the Court either been rejected or not been accepted by the judges. Despite the misgivings, the Court is still relevant and have certain contributions towards democracy. It has to a certain extent that enhances the working of checks and balances mechanisms among state organs. It is believed that the court could be more reliable and enhance its function in promoting democracy in the country by defining clearly classification of the subjectum litis as well as the objectum litis of the dispute that it may hear.